Overcoming the Challenges to Primary Healthcare and Universal Health Coverage in Nigeria: The Pivotal Role of the Family Physician - Ibrahim S. Bello; Abdulakeem A. Ahmed; Blessing T. Olaniyi; Fatai A. Olaniyan; Omowonuola O. Sonibare (Nigerian Frontline Medicine Journal)
BackgroundNigeria, the most populous country in Africa and the leading nation in sub-Saharan Africa, is facing a severe healthcare crisis. Its life expectancy of 62.2 years and other worsening health indicators, such as a maternal mortality rate of 814 maternal deaths per 100,000 live births, highlight a weakened health system. Although Family Physicians are the largest group of physicians in developed countries and have transformed primary healthcare, their role and involvement in Nigeria's health system are not yet fully realised. This review examines the main barriers to effective primary healthcare (PHC) and universal health coverage (UHC), and the role Family Physicians could play in achieving a strengthened PHC system.